2003
DOI: 10.1063/1.1602055
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding between water and methanol studied by temperature-programmed time-of-flight secondary ion mass spectrometry

Abstract: The interactions between condensed molecules at cryogenic temperatures (15–200 K) have been investigated on the basis of secondary ion mass spectrometry. It is demonstrated that the protonated molecular ions, emitted via the proton transfer reactions, provide us unique information about the reorganization of hydrogen-bonded molecules. From the CH3OH molecules adsorbed on the D2O–ice surface, the D+(CH3OH) ions are sputtered predominantly in the temperature range between 100 and 150 K since most of the CH3OH mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 30 publications
8
73
0
Order By: Relevance
“…In some cases it is considered hydrophobic and thus not involved in intermolecular interactions with either neighbouring CH 3 OH or H 2 O molecules 30,32,36,52 . In fact this appears to be the view held in the astronomy community where the role of the methyl group in intermolecular interactions is generally neglected.…”
Section: The C-h Stretch Regionmentioning
confidence: 99%
“…In some cases it is considered hydrophobic and thus not involved in intermolecular interactions with either neighbouring CH 3 OH or H 2 O molecules 30,32,36,52 . In fact this appears to be the view held in the astronomy community where the role of the methyl group in intermolecular interactions is generally neglected.…”
Section: The C-h Stretch Regionmentioning
confidence: 99%
“…Numerical simulations (Dougan et al, 2004;Morrone et al, 2006) and analysis of careful measurements (Guo et al, 2003;Soper et al, 2006) reveal networks of enhanced structure built from hydrogen-bonded water and methanol. Ultimately the behavior of methanol in water and on water surfaces depends sensitively on the balance between the molecules hydroxyl group which can participate in hydrogen bonding and its hydrophobic methyl group (Souda et al, 2003) and the specific topology of molecular level structuring (Morrone et al, 2006). Studies, specific to methanol layers on ice surfaces have observed stable monolayer coverages (Winkler et al, 2002;Jedlovszky et al, 2006).…”
Section: E S Thomson Et Al: Collision Dynamics and Uptake Of Watermentioning
confidence: 99%
“…When GZn 2+ complex comes in contact with methanol molecules, the highly associated aqueous GZn 2+ undergoes a structure breaking effect due to intermolecular hydrogen bonding between glycylglycine and methanol molecules. However, making and breaking of hydrogen bonds between water and methanol [26,30,31] is quite significant reflecting solvent-solvent interactions. Concluding from the above discussion, it is clear that amino group is not involved in metal-ligand complex formation and hence, it may be postulated as a binary ZnG + complex in which zinc is chelated to glycylglycinate through the carboxylate group.…”
Section: Viscosity Deviationsmentioning
confidence: 99%